Assessment of jugular endovascular malformations in chronic cerebrospinal venous insufficiency: colour-Doppler scanning and catheter venography compared with intravascular ultrasound. (December 2013) - Scalise, F; Farina, M; Manfredi, M; Auguadro, C; Novelli, E
Objectives: Chronic cerebrospinal venous insufficiency (CCSVI) is a malformative condition characterized by several anomalies of the azygos and/or internal jugular veins (IJVs). Recommended diagnosis of CCSVI is performed with colour-Doppler (CD) sonography. Though catheter venography (CV) is considered as the gold standard for determining vascular anatomy, its uniplanar point of view does not allow an overall evaluation of endoluminal structures. This limit could be addressed by intravascular ultrasound (IVUS). The aim of this report is to evaluate, in patients with multiple sclerosis (MS), the accuracy of CD sonography and CV versus IVUS in estimating the diameter and the cross-sectional area (CSA) of the IJVs and in detecting jugular endoluminal malformations (JEM). Method: Forty-five MS patients with CCSVI, diagnosed by CD sonography, were submitted to CV during IJVs angioplasty. Twenty-five subjects were also examined with IVUS. The IJVs maximum diameter (MAXD) and CSA were estimated. CD and CV data were compared with IVUS data with the Bland-Altman method. Results: The mean difference in IJV MAXD recorded by CD and IVUS was —0.5 mm. The mean difference in IJV MAXD recorded by CV and IVUS was 3.36 mm. The mean difference in IJV CSA recorded by CD and IVUS was —11.2 mm 2 . JEM recorded by IVUS were detected by CD sonography and CV with 88% and 32% accuracy, respectively. Conclusions: CV was significantly inferior to CD sonography and IVUS in detecting JEM. Differences between IVUS and CD sonography in detecting JEM and in quantifying jugular diameters were not significant. The IJV CSA was underestimated by CD sonography compared with IVUS. CD sonography was proven to be important in the anatomical characterization of CCSVI, providing useful information for correct intravascular treatment.